Moral distress among healthcare professionals in long-term care settings: a scoping review - Floor Vinckers; Elleke Landeweer (Philosophy, Ethics, and Humanities in Medicine)
Abstract Aim To explore the body of knowledge available regarding the moral distress of healthcare professionals in long-term care settings, focusing on influencing factors and strategies to cope with moral distress. Design Scoping review. Methods This scoping review follows the guidelines of the PRISMA-ScR protocol (Tricco et al. 2018) Searches were done using a strategy that included MeSH terms and free text terms. Data sources Data sources were PubMed, CINAHL, Psychinfo and Embase. Searches were done in October 2023 without any date restrictions. Results Eight articles were included in this review. Moral distress can impact the wellbeing of healthcare professionals. Influencing factors of moral distress of health care professionals appeared to be lack of resources, lack of communication and incongruence with colleagues. Strategies to cope with moral distress were talking about ethical issues with others, receiving support from colleagues and managers, and seeking support from outside the team or organization. Individual healthcare professionals relied on their personal characteristics or their professional identity and used rationalization, distancing themselves or acceptance of the situation to cope with their moral distress. Conclusion Moral distress of healthcare professionals in long-term care settings appears not differently experienced than moral distress among healthcare professionals in other healthcare settings. This can be beneficial in learning from each other, but also raises the question whether moral distress is too broadly defined. Impact This review addressed the scope and experiences of moral distress in long-term care settings. Future research can contribute to further insight into if and how specific features of long-term care are of influence on moral distress and formulate tailored strategies to lessen moral distress. Reporting method PRISMA-ScR.